Increased Thyroid Hormone Levels in Pesticide Sprayer at Agricultural Area - Pawitra, Aditya; Diyanah, Khuliyah Candraning; Latif, Mohd Talib; Susanto, Beni Hari; Lusno, Muhammad F D (UI Scholars Hub, 2022)
Pesticides used massively in the agricultural sector would cause many poisoning and serious health problems. Organophosphate pesticides have been identified as endocrine-disrupting chemicals. This study aimed to compare thyroid hormone levels between the sprayers chronically exposed to pesticides and the control respondents who had never been exposed to pesticides. This study was an analytical observational with a cross-sectional design. The total number of respondents was 150, 50 as sprayers and 100 as control respondents. The venous blood samples were examined using the Enzyme-Linked Immunosorbent Assay (ELISA). The findings significantly showed that the sprayer had a higher level of thyroid-stimulating hormone (TSH) (4.776 ± 1.1166), lower triiodothyronine (T3) (108.822 ± 18.810), and lower thyroxine (T4) (7.808 ± 1.067). Determinant factors among sprayers that significantly correlated to TSH levels was age (p-value = 0.006); work duration (p-value = 0.000); personal protection equipment (PPE) (p-value = 0.045); body position (p-value = 0.014); type of pesticides (p-value = 0.004), correlated with T3 levels was age (p-value = 0.037); body position (p-value = 0.045), correlated with T4 levels was age (p-value = 0.000); PPE (p-value = 0.045). It could be concluded that chronic organophosphate exposure would increase TSH and decrease T3 and T4.